motivation in teaching of applied mathematics to students of I.B.Trina Briseño Segovia (Revista Electrónica REDINE, 2018)
This research aims to analyze the influence of motivation in teaching applied mathematics students of the 4th Year Section "A" of the Bolivarian High School "Trina Briceño de Segovia" Parish Ramon Ignacio Mendez. Type the Modality Feasible research project supported by descriptive and field research was used. The population formed 34 students of the 4th year of that Bolivarian High School. As the sample was considered 100%. As an instrument structured questionnaire with Likert scale it was used. Diagnosis of problematisation: Causes that affect motivation: As part of the results showed the following stress (; 35.29%, A / V, 29% C / S); No diagnosis (C / N, 32.30%; N, 26.47%); based on difficulty (; 47% C / S) explanations; Use Test (A / V; 50%); Detection abilities (A / V; 53%); Doing exercises (C / S; 53%); Using models (C / S, 53%); Feasibility of Proposal: Existence of Material Resources, Human and Infrastructure.
Keywords: motivation; teaching learning; Mathematics